A Study of Changes and Innovation Paths in the Inheritance Models of Tai Chi in the Context of Social Change - Gu, Huimin; Han, Qing; Li, Hong; Li, Cuihan; Zhang, Jianwei; Lyu, Shaojun (The Journal of the International Society of Chinese Health Practices, 2025)
Abstract: At present, China is undergoing profound and extensive social changes. The process of industrialization and urbanization is accelerating, and information technology is reshaping people's lifestyles, values, and cultural ecology. As an important part of China's excellent traditional culture, Tai Chi is facing an unprecedentedly complex situation regarding its survival status, development path, and protection mechanism. Its inheritance in the current era is confronted with both opportunities and challenges. Objective: To systematically analyze the transformation and innovation strategies of Tai Chi's inheritance model under the background of social changes, through empirical research and theoretical analysis, to clarify the current characteristics of Tai Chi inheritance under the transformation of modern lifestyles, to analyze the realistic impact of social changes on Tai Chi inheritance, to sort out the current realistic difficulties in the protection and inheritance of Tai Chi, and to construct an innovative path for Tai Chi inheritance under the background of social changes. Method: By using research methods such as literature review, logical analysis, and field investigation, an in-depth analysis was conducted on the transformation of Tai Chi's inheritance model and the innovative path under the background of social changes. Result: On the one hand, modern lifestyles pose challenges to the inheritance and protection of Tai Chi. Due to the lag in the way Tai Chi is passed down, it is difficult for it to adapt to the pace of modern life. The "oral transmission and hands-on instruction" of traditional martial arts requires long-term learning under the guidance of a master. However, the fast-paced and fragmented nature of modern life makes it difficult for young people to devote sustained energy, resulting in a conflict between the master-apprentice system and the practice time. Moreover, traditional martial arts are often passed down from generation to generation within a family, but the urbanization process has accelerated the changes in family structure, resulting in the weakening of family inheritance. Secondly, the core techniques of Tai Chi are at risk of being lost. Taking Heze City as an example, the research found that there are a total of 35 traditional martial arts styles in the city, but only 5 styles have received relatively systematic protection, while the rest lack effective inheritance. The shrinking audience of martial arts practitioners has further exacerbated the fragmentation of the inheritance group. According to data from the Chinese Wushu Association, the number of martial arts schools across the country has decreased from 12,000 in 2010 to less than 6,000 in 2022. The insufficiency of financial support has also to some extent restricted the inheritance and development of core techniques. Liaocheng Shuicheng Middle School, as a non-material cultural heritage inheritance and education practice base recognized by the Shandong Provincial Department of Culture and Tourism, has not received financial support, and there are certain difficulties in the process of promoting and inheriting traditional martial arts. Moreover, the current chaotic teaching mode has to some extent affected the quality of Tai Chi Chuan's inheritance. Although Tai Chi has a high popularity, the quality of instructors varies greatly. Especially with the support of current platforms such as short videos and official accounts, due to the lack of effective supervision and the relatively low teaching threshold, some students have learned incorrect movements, resulting in injuries or misunderstandings of the principles of Tai Chi. Due to the impact of new sports events and traditional strong events, Tai Chi has insufficient appeal to the younger generation, resulting in a certain degree of group gap. Based on the sports consumption research data of multiple Chinese young people (aged 15-35) from 2024 to 2025, combined with the statistics of participation, search popularity, consumption trends and the development of emerging sports, it is found that running, basketball, badminton, comprehensive training and table tennis are the mainstream sports that young people like most at present. Rock climbing, skiing, paddleboarding, frisbee and other emerging trend sports have seen significant growth. The increase in these sports has further squeezed the inheritance and development space of Tai Chi among the younger generation. On the other hand, modern lifestyles have provided new opportunities for the promotion and dissemination of Tai Chi. Short-video platforms, with their huge user base and efficient dissemination mechanism, have provided an unprecedentedly broad stage for the spread of traditional martial arts. Through the algorithmic recommendation system, short videos related to Tai Chi are precisely pushed to interested users, breaking the time and space limitations of traditional dissemination and better promoting the spread of Tai Chi culture. Meanwhile, Tai Chi has been empowered by international competitions, promoting martial arts from the arena to cultural Windows. International competitions have become hubs for cross-cultural dialogue in Tai Chi. In the just-concluded women's Tai Chi and Tai Chi Sword final at the Chengdu World Games, Chinese athlete Lu Zhuoling won the championship, marking the first gold medal for the Chinese sports delegation. Her routine design links martial arts with popular culture, attracting the attention of international media. In the current context, the modern value and function of Tai Chi are gradually transforming. It not only retains its fundamental values of strengthening the body and promoting health, but also demonstrates new functions in cultural inheritance, international exchange, and innovative development. From the perspective of cultural dissemination, from the export of skills to dialogue among civilizations, from the perspective of industrial transformation, from single projects to the "culture, sports and tourism" ecosystem, from the perspective of health promotion, from the inheritance of experience to the development of evidence-based medicine. The rapid development of technology and media has also had a profound and complex impact on Tai Chi. The advancement of science and technology has provided unprecedented convenience and a broad platform for the inheritance, dissemination and innovation of Tai Chi, greatly enhancing its social influence and cultural popularity. At the 2025 World Humanoid Robot Games, robots precisely demonstrated movements such as "White Crane Spreading Its Wings" and "IP Man Squatting", expanding new scenarios of human-robot collaboration and showcasing the boundless possibilities of Tai Chi's development in future life. The media has provided a real opportunity for the cultural promotion of Tai Chi to break through its boundaries. During the "Suzhou Super League" football match in Nanjing, students from seven countries performed Tai Chi in front of tens of thousands of spectators. A Bangladeshi student said that through the performance, he gained a deeper understanding of the philosophy of Tai Chi. Sports events have become an efficient medium for the international dissemination of Tai Chi. Conclusion: Research on the Innovative Path of Tai Chi Chuan Inheritance, Development and Innovation under the Background of Social Change. Promote technological and digital empowerment, utilize high-precision motion capture technology to collect the routines, techniques and force application characteristics of representative inheritors, and establish a digital gene bank of Tai Chi that includes multi-dimensional data such as movement trajectories, strength and breathing rhythms. High-definition scanning and digital storage of ancient Tai Chi manuals, historical images and documentary materials are carried out to build an online accessible digital museum of Tai Chi. Integrate high-quality digital resources to create a comprehensive Tai Chi cloud platform that combines online courses, live teaching, community communication, and AI evaluation, breaking down the geographical barriers of high-quality teaching resources. Build an international communication system and carry out in-depth cooperation with overseas educational institutions, such as jointly setting up workshops with renowned foreign universities, Confucius Institutes and community colleges, and incorporate them into the overseas Chinese language teaching system. In addition to actively striving to perform in various international events such as sports meets and world expos; Establish official accounts on international mainstream social platforms such as YouTube and Instagram, and post short video content customized according to the cultural preferences of different regions. Promote the integration of the industrial ecosystem, cooperate with health management institutions and elderly care communities, jointly develop "exercise prescription" courses for specific chronic disease or sub-healthy people, and establish an effect evaluation system. To stimulate the identity of the younger generation, in response to the fast-paced life of young people, develop lightweight and interesting products, design short video courses such as 5-15 minute office Tai Chi and Tai Chi during breaks, as well as develop mobile applications with points and check-in functions, to promote the innovation of Tai Chi content and forms.